Energetic synchrony throughout the non‐breeding season in common guillemots from four colonies. (14th February 2023) - Buckingham, Lila; Daunt, Francis; Bogdanova, Maria I.; Furness, Robert W.; Bennett, Sophie; Duckworth, James; Dunn, Ruth E.; Wanless, Sarah; Harris, Michael P.; Jardine, David C.; Newell, Mark A.; Ward, Robin M.; et al.
Abstract : The non‐breeding season presents significant energetic challenges to birds that breed in temperate or polar regions, with clear implications for population dynamics. In seabirds, the environmental conditions at non‐breeding sites drive food availability and the energetic cost of regulatory processes, resulting in variation in diet, behaviour and energetics; however, very few studies have attempted to understand if and how these aspects vary between populations. We investigated whether non‐breeding location influenced diet, behaviour and energetics in the common guillemot Uria aalge . We studied guillemots from four UK breeding colonies, two located on the west coast of Scotland and two on the east. We quantified non‐breeding distribution, foraging behaviour and activity budgets of 39 individuals from July to March, using geolocation–immersion loggers and time‐depth recorders, and used feather stable isotope signatures to infer diet during the post‐breeding moult. We calculated energy expenditure and investigated whether the peak (an indicator of the potential vulnerability to marine threats) varied between colonies. Individuals were spatially segregated according to the coastline they breed on, with west coast guillemots distributed off the west coast of the UK and east coast guillemots distributed off the east coast. Diet and behaviour were more similar in guillemots that shared a breeding coastline than those that did not, as west coast guillemots foraged at a lower trophic level, spent less time diving and engaged in more pelagic foraging than east coast guillemots. However, energy expenditure was remarkably similar between colonies, peaking during late February/early March, indicating that, during our study period, there was high synchrony between colonies in the timing of potential vulnerability to marine threats. Therefore, any anthropogenic changes that result in decreased food availability or increased energy expenditure during late winter may have greater impacts on energy balance, with consequences for population dynamics.